Work-family enrichment and psychological health - Ameeta Jaga; Jeffrey Bagraim; Zahira Williams (SA Journal of Industrial Psychology, 2013)
Orientation: This study examines the beneficial aspects of the interface between work and family and its relationships with psychological health from a positive psychology perspective. Research purpose: The objective of this study was to investigate whether work-family enrichment helps to predict psychological health, specifically increased subjective well-being and decreased feelings of emotional exhaustion and depression.